Psicoterapia basada en Mindfulness: impacto de un contexto postpandemia sobre la calidad de vida de docentes - Santos Morocho, Jose (2024)
Introduction: Mindfulness, as a third generation psychotherapy, focuses on present moment awareness. This study has a cultural and socioeconomic diversity of the population allowing to know how Mindfulness promotes emotional well-being in times of crisis. Objective: to determine the effectiveness of Mindfulness to improve the quality of life of teachers. Material and methods: descriptive-explanatory study, using a pretest and retest design with a quantitative approach. The sample was non-probabilistic, composed of 50 teachers, selected by convenience sampling. A form was designed with demographic variables and GHQ-28 test. The data obtained were processed using the SPSS V 22.00 statistical program. Conclusion: the quality of life before and after the application of the intervention plan was significant. The application of mindfulness is recommended as an effective intervention to mitigate psychological distress in specific contexts.   Keywords: Mindfulness; Psychotherapy; Quality of Life; Post pandemic; Covid 19; Teachers.